THE USE OF PROJECT BASED LEARNING AND PEER ASSESSMENT TO IMPROVE STUDENTS’ SPEAKING SKILL FOR YOUNG LEARNERS - Dwi Endah Widyastuti (ABNUS Publisher, 2021)
Project Based Learning is a learning method to encourage knowledge building through collaborative learning and usually integrated with real world concerns. Peer Assessment is an effective way to may help learners reflect on their own project work and improve their speaking skill. In addition the peer-assessment is useful as guidance for the students’ projects. This research aimed to find out the impact of project based learning and peer assessment learning to improve students’speaking skill and the benefits of PBL and Peer Assessment. This research was conducted at the seventh grade of SMPN 2 Babelan-Bekasi, from 12 September until 10 October 2017. It involved only one class is the students of VII.1 in SMPN 2 Babelan-Bekasi. This class consists of 30 students with 17 females and 13 males. This research was a classroom action research that consist of three cycles. Each cycles has four steps, they are; planning, acting, observing and reflecting. The researcher answered the research questions by using four instruments such as observation, interview, test and questionnaire. The results of this research revealed that first, PBL and Peer Assessment could improve students` speaking skill. Second, talked a lot, they were participating each other, it motivated them to speak more, to be an enthusiasm and to be independent learner. Besides, the number of errors in speaking components was significantly decreased after they were encouraged to assess by peer. Based on the theories and previous studies, it can be concluded that there were positive effects; the peer assessment which apply in Project Based Learning (PBL) has positive in teaching speaking. Peer assessment helped the students in speaking English and peer corrective about their performance, so it built their motivation in developing of speaking skill.